Assessment of vitamin D, calcium, inorganic phosphate, alkaline phosphatase and parathormone in juvenile idiopathic arthritis patients (Bangladesh Journal of Child Health, 2020)
Background: Decrease in bone mass in JIA patients is multifactorial. By assessing the level of vitamin D and other associated parameters we can identify the deficiency earlier and can predict the risk of osteoporotic bone fracture & give appropriate supplements.Objective: To determine the status of serum 25(OH)D, calcium, inorganic phosphate, alkaline phosphatase and parathormone in patients with JIA.Materials and methods: It was a cross sectional study. Thirty newly diagnosed cases of JIA attending the pediatric rheumatology clinic of Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka from October 2015 to September 2016 were included. Thirty age and sex matched control were also selected. Serum 25(OH)D, calcium, inorganic phosphate, alkaline phosphatase & parathormone were assesed in both cases and controls.Results: Hypovitaminosis D was present in 60% of JIA and 33% of controls. In JIA group the mean level of all biochemical parameters were significantly lower than control group except serum 25 (OH) D. Level of calcium, inorganic phosphate and alkaline phosphatase was decreased with the decrease of 25 (OH) D levels and there was no change of parathyroid hormone level.Conclusion: More than half of JIA patients had hypovitaminosis D. There was positive relationship between 25(OH)D level and other biochemical parameters except PTH.Bangladesh J Child Health 2019; VOL 43 (3) :145-151